Syphilis in pregnant women: implications of diagnosis revelation and partner notification strategies - Rocha, Ana Fátima Braga; Araújo, Maria Alix Leite; Barros, Valéria Lima de; Oliveira, Ana Karinne Dantas de (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: The low percentage of sexual partners of pregnant women with treated syphilis is one of the main obstacles to the control of congenital syphilis. Objective: To analyze the notification of the syphilis diagnosis to the sexual partner of the pregnant woman, its implications and the suggested summoning strategies. Methods: This is a qualitative research conducted in Fortaleza, State of Ceará, from April to October, 2014. A total of 14 women reported with syphilis during prenatal care and nine sexual partners were interviewed. The thematic content analysis and the idea association tree were used to analyze and reveal the results. Results: Pregnant women prefer to communicate the diagnosis to their partner, but they say they need help from the professional for this moment. Among the partners there was no consensus about this strategy, as it generates conflicts for the couple. They therefore indicated other means of communication considered more appropriate. It was found that there is no ideal model of notification of sexual partner of pregnant woman with syphilis. Conclusion: According to the interviewees’ reports, we can conclude that the best way is the one that considers the relationship context and the singularities informed by the patients.